Analisis Faktor Kunjungan Wisatawan Mancanegara dan Tingkat Penginapan Hotel Terhadap Penerimaan Pendapatan Asli Daerah (PAD) Sub Sektor Pariwisata pada Industri Pariwisata di Daerah Istimewa Yogyakarta (DIY) Tahun 2007-2018 - Marie, Andhalia Liza; Widodo, Rintis Eko (Jurnal Ilmiah Pariwisata; Vol 25 No 3 (2020): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v25i3.1413, 2020)
This study aims to analyze the factors of foreign or foreign tourist visits and hotel occupancy rates on the income of the tourism sub-sector in the tourism industry in DIY from 2007 to 2018 which aims to determine how much influence the number of foreign tourist visits. tourist visits. or foreigners and the level of lodging in hotels to revenue from the PAD sector in the tourism sub-sector in DIY Province for the period 2007-2018. This research is descriptive and associative, the data used in this study are secondary data in the prone period 2007 to 2018 which were obtained from the Yogyakarta Province Central Bureau of Statistics and the Yogyakarta Provincial Tourism Office. The analytical tool used in this research is multiple regression analysis techniques. The results of the study found that there was a positive influence between the number of foreign tourists visiting and the level of hotel lodging on the revenue revenue of the tourism sub-sector in Yogyakarta in 2007-2018. Keywords: Tourist Arrival; Foreign Tourist; Hotel Room Occupancy; Regional Income From The Tourism Sub Sector.